Heterophile antibodies, false-positive troponin, and acute coronary syndrome: a case report indicating a pitfall in clinical practice. Issue 2 (4th February 2021) - Lakusic, Nenad; Sopek Merkas, Ivana; Lucinger, Daren; Mahovic, Darija
Abstract: Background: Heterophile antibodies are one of the most common causes of false-positive troponin. Case summary: We report a case of a 53-year-old woman with false-positive troponin elevation and a clinical presentation understood and treated as non-ST-elevation acute coronary syndrome. Because of chronic basal elevation of troponin (at a 'plateau' level) and chest pain, the patient underwent several invasive coronary angiograms until false-positive increase of troponin due to heterophile antibodies was suspected. Borderline stenosis of a left circumflex coronary artery found on first coronary angiogram was a coincidental finding and heterophile antibodies in the patient's serum were confirmed. Discussion: This interesting case report aims to remind the clinicians about the possibility of false-positive troponin level due to laboratory analytical interference caused by heterophile antibodies. In this case, it is important to suspect false-positive troponin elevation, even when coronary artery disease is found. This rare and less mentioned and/or recognized cause of troponin elevation may lead to unnecessary invasive diagnostics and aggressive treatment of patients.